Exploring Motivational Factors Influencing English Learning in a Saudi University - Chaudhary, Anjum (International Journal of Language and Literary Studies, 2024)
This research article aims to explore the motivational patterns of students from two different academic streams in the EFL context. To achieve this purpose, the perception, motivation level, and proficiency in the context of English as a Foreign Language (EFL) are investigated. The classroom study was conducted with a mixed-methods approach, combining quantitative surveys and qualitative interviews to gather comprehensive insights. To gather data, a triangulated method is employed, involving the use of a questionnaire, semi-structured interviews, and classroom observations. The subjects are the two groups of students from the first term of the academic year 2023-24 who are registered under different majors but studying the same English program in their first year of university. To explore the connection between motivation levels and proficiency in the second language (L2), the cumulative percentage scores from formative and summative assessments are analyzed. The results indicate a significant correlation between learners’ motivation levels and their proficiency in the second language. However, when comparing academic achievements between the two groups, it is evident that group A significantly outperformed group B. The study is relevant for educators and learners as it adopts a practical and principled approach. Moreover, it provides updated insights into current perspectives on motivation in language learning.